Prognostic values of the mRNA expression of natural killer receptor ligands and their association with clinicopathological features in breast cancer patients - Abouelghar, Ali (Oncotarget, 2018)
BACKGROUND: Natural killer (NK) cells are lymphocytes of the innate immune system that have potent cytotoxic activity against tumor cells. NK cell recognition and activity towards cancer cells are regulated by an integrated interplay between numerous inhibitory and activating receptors acting in concert to eliminate tumor cells expressing cognate ligands. Despite strong evidence supporting the role of NK cells in breast cancer (BC) control, BC still develops and progresses to form large tumors and metastases. A major mechanism of BC escape from NK immunity is the alteration of the expression of NK receptor ligands. The aim of this study was to determine whether NK receptor ligands’ mRNA expression might influence prognosis in BC patients and whether these effects differ by molecular subtypes and clinicopathological features. METHODS: We used the KM plotter platform to analyze the correlation between mRNA expression of 32 NK receptor ligands and relapse-free survival (RFS) and overall survival (OS) in 3951 and 1402 BC patients, respectively. The association with tumor subtypes and clinicopathological features was determined. BC samples were split into high and low expression groups according to the best cutoff value and the two patient cohorts were compared by Kaplan–Meier survival plots. The hazard ratios with 95% confidence intervals and log rank P values were calculated and FDR-adjusted for multiple testing correction. The data was considered to be statistically significant when FDR-adjusted P value < 0.05. RESULTS: High mRNA expression of around 80% of ligands for NK activating and inhibitory receptors associated with better RFS, which correlated with longer OS for only about half of the NK-activating ligands but for most NK-inhibitory ligands. Also, five NK-activating ligands correlated with worse prognosis. These prognostic values were differentially associated with the BC clinical criteria. In addition, the favorable prognostic influence of NK-activating ligands’ upregulation, as a whole, was mainly significantly associated with HER2-positive and basal-like subtypes, lymph node positive phenotype, and high-grade tumors. CONCLUSIONS: NK receptor ligands appear to play an important role in defining BC patient prognosis. Identification of a group of patients with worse prognosis expressing high levels of NK-activating ligands and low levels of NK-inhibitory ligands makes them ideal potential candidates for NK-based immunotherapy to eliminate residual tumor cells, prevent relapse and improve patient survival.